Response of upland rice to ploughing depth, potassium fertilization, and soil water status - Stone, Luis Fernando; Moreira, José Aloisio Alves (Pesquisa Agropecuaria Brasileira, 1996)
The effects of K levels (0, 40, 80, and 120 kg of K 2 O/ha), K split application (with and without), ploughing depth (10-15 cm and 30-35 cm), and water stress (with and without) on the yield of upland rice were studied during two years. In the absence of a soil compacted layer rice yield was higher, independentlyof soil water status, when the soil was ploughed, at 10-15 cm deep. This ploughing depth promoted higher nutrient concentration in the surface layer. In soil with high K level, under water stress, the yield of the rice cultivar Rio Paranaffia increased with increasing K level, whereas the yield of 'CNA 6843- 1' was not significantly affected, because a more severe effect of the water stress. Under non water-stress there was no response to K levels. The lack of response to K split application can be explained by the fact that K leaching was not so high due to rice sowing after the period of more intense rainfall.